Indikasi Kegagalan Pembangunan Berkelanjutan dari Implementasi Program CSR - Hery Purnomo (Jurnal Syntax Admiration, 2024)
The presence of multinational companies entering Indonesia has both positive and negative impacts on the communities around the company. The positive impacts that arise include the emergence of new jobs, new economic growth. The negative impacts that arise include environmental damage, pockets of poverty, crime and others. Efforts made by the company to reduce the negative impacts resulting from company activities through CSR programs. The CSR program run by the company adheres to a sustainable development approach where the company's activities do not interfere with the continuity of life for the next generation. A popular approach is the triple bottom line, namely a balance between people, planet and profit. In reality, the activities carried out through the CSR program have not had a positive impact on society, in fact there are still many negative impacts. This article attempts to examine why the implementation of CSR carried out by companies has not been able to provide positive results to society, especially in sustainable development efforts, what factors are behind sustainable development not being realized. The research method usesSystematic Literature Review (SLR). The results and discussion are that the existence of multinational companies in Indonesia in processing natural resource wealth does have big implications. The CSR concept that is developing with the idea of ​​sustainable development is a breath of fresh air in the development of this nation. But in reality, the CSR program that was implemented then fell short of expectations. The sustainable development campaign promoted by the company in the form of CSR is still limited to perpetuating the company's interests. The idea of ​​strong capitalism by multinational companies must be controlled by this country, especially the role of government and civil society.